Atraumatic Bilateral Patella Fracture in Middle-Aged Female: A Rare Case Report - Ishwor Ghimire Padhya; Saral Lamichhane; Pramod Devkota; Praful Gurung; Pragya Aryal (Case Reports in Orthopedics)
The patella is the largest sesamoid bone in the body and an important structure of the extensor apparatus which is under undue stress during flexion and extension of the knee. Bilateral fracture of the patella without trauma is a very rare event and may be multifactorial without a single cause. A repetitive stress reaction in a previously predisposed bone can be an important cause. We report a case of a 45-year-old female with a nontraumatic bilateral transverse patella fracture with loss of extensor mechanism. A stable surgical fixation for such a displaced fracture with a good rehabilitation program can lead to a good functional outcome.